코퍼스 분석을 기반으로 한 『빌레트』의 서술적 특징 연구 - 박순강(Soon-gang Park) (영미연구, 2025)
샬럿 브론테의 『빌레트』는 주인공이자 서술자인 루시 스노우의 감정적 성장과 발전을 극화한 1인칭 서사 성장소설로 빅토리아시대 가정 이데올로기에서 소외된 여성의 삶을 재현한다. 내러티브에서는 그녀의 억눌린 욕망과 외로움, 열망, 좌절 같은 다양한 감정이 정교하게 서술되고 개인적 경험은 면밀한 관찰의 시선으로 보편적 정서를 반영해 확장된다. 또한 자기부정으로 대표되는 서사적 회피와 부인은 여성 주체가 감정을 표출하고 자아를 확립해가는 과정을 재현하기 위한 서사 기법이 된다. 코퍼스 언어학은 이러한 서사적 특징을 분석해서 그 고유한 문체적 특징이나 언어패턴들을 객관적으로 확인할 수 있도록 돕는다. 이에 본 연구는 코퍼스 분석을 통해서 『빌레트』의 서술적 특징을 확인, 두드러진 부정어의 빈도를 확인할 수 있었다. 이로써 브론테가 의도적으로 부정어휘를 사용해 루시의 서술을 모호하게 만들어 불확실성을 강조하고 그 진술의 진위를 의심하게 하지만 역설적으로 이러한 전략을 통해 주도적 서사를 이끌어나가는 동력이 됨을 알 수 있다. 등장인물들의 이름과 시각적 행동과 관련된 어휘들도 높은 출현빈도를 보이는데, 이를 통해 루시가 소외되고 한정된 역할에서 벗어나 타인에 대한 높은 관심으로 그들과 소통하려는 의지가 있음을, 또 시각적 반응에서 그치지 않고 그 시선을 감정 어휘와 함께 사용함으로써 가시화시켜 보다 분명한 감정이입을 도모하고 있음도 확인할 수 있다. 무엇보다 높은 빈도의 부정어휘를 통해 불성실한 서술자로 규정되는 루시의 서사 전략이 회피, 지연, 침묵으로 재현되고 전략적으로 이를 활용해 주체적 태도를 강화하고 있음도 알 수 있다. 그러나 이러한 서사적인 특징은 코퍼스 분석의 정량적 분석 결과만으로는 직관적으로 파악할 수 없고 정성적인 해석을 병행할 때만 의미 있는 결과로 이어질 수 있다. This study analyzes the narrative strategies in Villette, a psychological Bildungsroman that explores the emotional development and self-awareness of its narrator and heroine, Lucy Snowe, using a corpus-based approach. Corpus linguistics helps reveal what makes the author’s narrative style unique by analyzing the language patterns in the texts. In Villette, Charlotte Brontë emphasizes the uncertainty by deliberately using negative words and non-factive verbs like seem in the narrative, creating ambiguity. This deliberate ambiguity causes readers to question the veracity of her retrospective narration. Moreover, narrative evasion and denial, exemplified by Lucy Snowe’s self-negation, are the key narrative strategies that illustrate the female protagonist’s struggle to express her emotions and define her identity within a patriarchal society. She carefully observes others in silence, driven by a desire to understand and connect with them despite the alienation and neglect she experiences. This is further identified by the frequent use of the character names and vision-related words, such as eye and perception verbs. However, this aspect cannot be identified through quantitative findings from the corpus even though her repressed desire, complex emotions such as loneliness, distress and frustration are deliberately narrated and developed through her detailed observation. These narrative strategies in Villette can be meaningfully interpreted when accompanied by qualitative analysis. Thus, when applying corpus linguistics to literary interpretation, the qualitative observation should not be overlooked. KCI Citation Count: 0